Study on E-Learning in Organizations and its Effectiveness on Employees - Chong, Nicholas How Keat (2014)
Learning is a life-long process which happens both consciously and subconsciously. Learning stimulates part of the brain called synapse, cortex and neuron where human beings somehow put things together on how things work, therefore completing the process of learning. In a more practical approach, learning is method that enables human being to be successfully involved in their life and its surrounding. While learning can come naturally to human beings such as learning to walk and to speak, the subject of learning can be determined by its learner as its boundaries are limitless. Growing up, one has experienced learning in many factors. It can by guidance ( mentoring, coaching and teaching ), experience ( observation, training ), enforcement ( memorizing, rules and regulation ) and many more. The media of learning has also evolved over the years. Documentation of observations and events, opinions and experiments have come in the form of books, which is the most common medium during school days. Classroom teaching also comes hand in hand to complement the books supplied in school. Television also became a mass medium in learning in TV programs, documentaries and even cartoon program/TV shows, although how beneficial it is has been a subject of debate for decades. As the computer era takes over, learning via computer has also become popular and is still evolving. From computer based environment, internet has taken over and learning is now done electronically. The topic of this research is on e-learning, in the context of organizations and how it can be effective on employees. The aim of this research is to put E-learning on the map, where it is already a mature concept given the technology advancement of the foundations for E-learning ( high speed internet and advance electronic graphics technology ). It is with the hope that E-learning can be an important and effective aspect of learning in areas where it can either be a better alternative to conventional learning or in areas where it can complement conventional learning in order to enhance overall learning experience of the learners.